Essentials of Rorschach assessment comprehensive system and R-PAS - Gurley, Jessica R. (2017)
"The clinician's practical guide to both methods of Rorschach personality assessment Essentials of Rorschach Assessment provides an invaluable resource for clinicians, offering the only step-by-step guidance toward all aspects of the Rorschach Comprehensive System and Rorschach Performance Assessment System (R-PAS). Beginning with an overview of the tests' history and development, the discussion delves into each test separately before placing the two side by side for direct comparison of administration, coding, and interpretation. The same case study is used for both tests, providing a start-to-finish example of how the Comprehensive System and R-PAS differ, and practical resources including checklists, charts, and sample forms help ease implementation, use, and transition. Thorough explanations break down the jargon and technical language to give clinicians a clearer understanding of both tests without sacrificing precision or depth of information, providing a quick and easy reference for Rorschach personality assessment. While the Rorschach Comprehensive System is the most established version of the inkblot test, the recent development of R-PAS provides an alternative that may be more advantageous in some situations. This book provides complete guidance toward both tests, with expert advice on transitioning between the two. Understand the theoretical underpinnings of the Rorschach systems Learn how to administer, score, and interpret the tests effectively Compare the Rorschach Comprehensive and R-PAS through side-by-side case studies Access useful resources for coding, scoring, administration, interpretation, and more The Rorschach Inkblot Test assesses unconscious perceptions, thought processes, needs, motivations, and conflicts without relying on self-reporting, and can be useful in assessing an individual for severe mental illness. Essentials of Rorschach Assessment brings clinicians up to speed quickly and easily to help them get the most out of the system"--Provided by publisher.
"Essentials of Rorschach Assessment: Comprehensive System and R-PAS discusses the benefits of the Rorschach and provides an overview of the history of the Rorschach, from Rorschach's initial conceptualization of the test through the development of the R-PAS. The book includes separate sections on the Comprehensive System, the R-PAS, and a shorter section that compares the two systems. Both the sections on the Comprehensive System and the R-PAS have chapters dedicated to the administration, scoring, and interpretation of the systems. -Breaks down the jargon and technical language of the Rorschach systems to improve understanding. -Includes a sample case for each system that allows the reader to see a case from start to finish (administration to interpretation and the final report). The same case sample is used for both systems; this allows the reader to compare the systems directly and to see the differences between the systems in administration, coding, and interpretation. -Provides useful resources including sample forms to help with administration, coding, and interpretation; checklists to use when scoring and interpreting to reduce the chance of mistakes; charts that compare the two systems to help the reader transition between the systems"--Provided by publisher.
Machine generated contents note: Preface Chapter 1: Overview and History of the Rorschach Technique The Rorschach History of Rorschach Test Yourself Chapter 2: Comprehensive System: Administration Preparing to Administer the Rorschach CS What Is Needed for a Valid Administration Administering the CS Accomodating Individuals with Disabilities and Using Interpreters Summary of Administration Test Yourself Chapter 3: Comprehensive System: Scoring Location Developmental Quality - DQ Determinants Form Quality Contents Populars Organizational Activity (Z Scores) Special Scores Summary on Coding Test Yourself Chapter 4: Comprehensive System: Interpretation Interpretation of Controls and Stress Tolerance Interpretation of Situationally Related Stress Interpretation of Affect Interpretation of Information Processing Interpretation of Cognitive Mediation Interpretation of Ideation Interpretation of Self Perception Interpretation of Interpersonal Perception Summary of CS Interpretation Test Yourself Chapter 5: Comprehensive System: Case Sample Background Information Administration Coding Interpretation Summary and Recommendations Test Yourself Chapter 6: R-PAS: Administration Preparing to Administer R-PAS What Is Needed for a Valid Administration Administering R-PAS Accomodating Disabilities and Using Interpreters Summary of Administration Test Yourself Chapter 7: R-PAS: Coding Things to Remember Before Coding an R-PAS Protocol Coded Response Behaviors Location Codes and Numbers Coding Location Numbers Space Responses Content Codes Object Qualities Pairs (2) Form Quality (FQ) Populars Determinants Special Scores Scoring Platform Summary of Coding Test Yourself Chapter 8: R-PAS: Interpretation Interpretation Page 1 Page 2 Variables Summary of Interpretation Test Yourself Chapter 9: R-PAS: Case Sample Background Information Administration Interpretation Summary and Recommendations Test Yourself Chapter 10: Comparison of the CS and R-PAS: Strengths and Weaknesses of Both Systems Standardization and Norms Reliability and Validity Administration Coding/Scoring Interpretation Comparison of the CS and R-PAS Final Thoughts on the CS and R-PAS Test Yourself Appendix A: Sample Sequence of Scores and Structural Summary Reports Sequence of Scores and Summary of Approach Structural Summary Constellations References About the Author.
Includes bibliographical references (pages 355-360) and index.
Keywords: Rorschach Test; PSYCHOLOGY / Assessment, Testing & Measurement